Age-Unfriendly by Design: Built Environment and Social Infrastructure Deficits in Greater Melbourne. Issue 1 (2nd January 2023) - Hartt, Maxwell; DeVerteuil, Geoff; Potts, Ruth
Abstract: Problem, research strategy, and findings: The world's population is aging at a rapid rate, yet many local built and social environments are not well suited to support older adults. Australia exemplifies the demographic–environmental disconnect because it is one of the world's most suburban nations and has one of the proportionally largest baby boom generations. In this research we examined the relationship between built and social environments with respect to older adult vulnerability in Greater Melbourne (Australia). We found that neighborhoods with lower levels of built environment support also had lower levels of social infrastructure. The spatial imbalance across the region was most pronounced when considering the spatial distribution of older adults aged 85 years and older. Our analysis of policymaker interviews revealed a marked disconnect between the scale and scope of the challenges of suburban aging and the state and local government response. Limitations of the study included the operationalization of built environment and social infrastructure variables. Takeaway for practice: Age-friendly planning and design cannot be limited to the "easier stuff" such as communication and information, social participation, and respect and inclusion. Suburban built environments require more effort and investment in transportation, housing, and outdoor spaces and buildings to support the physical and mental wellbeing of older adults aging in place. Walkable suburban neighborhoods with high levels of accessible social infrastructure will help build community connections and encourage older adult physical activity and social engagement.